2015
DOI: 10.1007/s12035-015-9428-3
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Promotes a Conversion of Astrocytes into Neural Progenitor Cells via NF-κB Activation

Abstract: Brain inflammation, a common feature in neurodegenerative diseases, is a complex series of events, which can be detrimental and even lead to neuronal death. Nonetheless, several studies suggest that inflammatory signals are also positively influencing neural cell proliferation, survival, migration, and differentiation. Recently, correlative studies suggested that astrocytes are able to dedifferentiate upon injury and may thereby re-acquire neural stem cell (NSC) potential. However, the mechanism underlying thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 53 publications
(67 reference statements)
5
48
0
1
Order By: Relevance
“…The protective effects on oligodendrocytes and inhibition of reactive astrocyte proliferation/reactive gliosis, promoted via NF‐κB activation (Gabel et al. ), achieved functional recovery of EAE clinical symptoms in all treated groups.…”
Section: Discussionmentioning
confidence: 97%
“…The protective effects on oligodendrocytes and inhibition of reactive astrocyte proliferation/reactive gliosis, promoted via NF‐κB activation (Gabel et al. ), achieved functional recovery of EAE clinical symptoms in all treated groups.…”
Section: Discussionmentioning
confidence: 97%
“…Astroglia may induce neurogenesis from adult stem cells . Inflammation‐induced NF‐κB activation promotes the conversion of astrocytes into neural progenitor cells . Proliferation results in an increase in the number of astrocytes which must not be mistaken for the mere enhancement of GFAP expression in already existent astrocytes.…”
Section: Reactive Astrogliosismentioning
confidence: 99%
“…Surprisingly, we found that only 2 cytokines, namely IL-17D and IL33, co-upregulated with Cx43/GJA1 in spinal cord periplaque areas. Other inflammation-related genes comprised notably CD44 and CD200 that were both previously demonstrated on reactive astrocytes [37,38]. Finally, the GJA1/Cx43 module comprised several ECM-related genes that are expressed by …”
Section: A Unique Set Of Genes Co-upregulate With Cx43/gja1 In Periplmentioning
confidence: 85%